Association between waiting time for radiotherapy initiation and disease progression among women with cervical cancer in Addis Ababa, Ethiopia. Issue 6 (22nd June 2021) - Dereje, Nebiyu; Addissie, Adamu; Worku, Alemayehu; Gebremariam, Alem; Kantelhardt, Eva Johanna; Assefa, Mathewos; Jemal, Ahmedin
Abstract: There is shortage of radiotherapy machines in low‐income countries, including Ethiopia. Data on adverse effects of this on cancer outcomes are limited, however. Herein, we examined the extent of waiting time for radiotherapy and its association with disease progression based on a prospective cohort study of women diagnosed with stage IA‐IVA cervical cancer in Addis Ababa and who were scheduled to receive radiotherapy at Tikur Anbessa Specialized Hospital, the only hospital that provides radiotherapy services in the country. Association was examined using Multivariable mixed effects logistic regression model. Among the 178 women with cervical cancer scheduled for receipt of radiotherapy and with vital status information, 16 deceased (9.0%) while waiting for radiotherapy. For the remaining 162 women who initiated radiotherapy, the median treatment waiting period was 137 days (IQR = 60‐234 days), with 74.1% of women waiting for >60 days. Tumor progressed to higher stage for 44.4% of these women. Compared to those women who initiated radiotherapy ≤60 days after diagnostic confirmation, the odds of tumor progression to higher stage was three times higher in those women who initiated radiotherapy between 120‐179 days (aOR =3.30, 95%CI: 1.18‐9.27) and ≥180 days (aOR =3.06, 95%CI: 1.24‐7.52). Waiting period for receipt of radiotherapy among women with cervical cancer is exceedingly long in Addis Ababa, and it is associated with disease progression to higher stages. These findings reinforce the need to expand radiotherapy infrastructure in order to mitigate the undue high burden of the disease in Ethiopia and other parts of Africa.